Adermatoglyphia in inherited skin disorders. Systematic review. - Alsabbagh, M. (European Journal of Pediatric Dermatology, 2023)
Adermatoglyphia (ADG) or absence of ridges on the pads of the fingers and toes is a rare condition that can be acquired. However, it can also be the expression of inherited skin disorders, most frequently of Basan syndrome. The current report makes a systematic review of the literature, finding 90 cases of ADG in subjects affected by various inherited skin disorders.